Consumers' privacy concerns and implications for a privacy preserving Smart Grid architecture—Results of an Austrian study. (September 2015) - Döbelt, Susen; Jung, Markus; Busch, Marc; Tscheligi, Manfred
Abstract: Smart Grid applications, such as energy feedback systems, load shifting for smart homes, and smart charging of electric vehicles provide new possibilities to support the incorporation of renewables. Aside from technical feasibility, consumer requirements and concerns, particularly in terms of the protection of personal privacy, have not been the focus of Smart Grid developments. We therefore investigated consumers' Smart Grid related privacy concerns in private and business contexts and focused on the research questions: (1) who is perceived as a trustworthy authority for energy data storage? (2) What can pose as a privacy threat for consumers? (3) How should energy data be handled by an ICT infrastructure? We conducted a comprehensive online survey ( N = 240) in Austria to gain an overview into the concerns and deepened our understanding by conducting two focus groups ( N = 15). Our results indicate the importance of decentralized data storage, access control, as well as information transparency and the incorporation of privacy enhancing functionalities. Consumer-driven requirements and technical requirements led to a suggestion for a privacy preserving ICT infrastructure, following the paradigm of a service-oriented architecture. This architecture can serve as a reference for a future user-centered Smart Grid ICT architecture design.